10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Background Improving survival after liver transplantation has increased pregnancy rates among women of reproductive age, raising critical questions about breastfeeding safety with maintenance immunosuppressants. Quantitative human data on everolimus transfer into breast milk remain extremely limited. Methods Pharmacokinetic assessment of everolimus (0.25 mg/day once daily) was performed in a woman postpartum day 5 after cesarean delivery. Maternal whole-blood and breast milk samples were collected under steady-state conditions. Whole-blood concentrations were measured by automated immunoassay; breast milk concentrations were quantified by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Results Maternal whole-blood concentrations peaked at 4 hours (1.98 ng/mL). Breast milk concentrations showed a delayed peak at 9 hours (0.117 ng/mL). Using the linear trapezoidal method, the milk-to-whole-blood AUC0-24 ratio was 0.078, and the estimated relative infant dose (RID) was 0.30%. Conclusion This first liver transplant case demonstrates minimal transfer of everolimus into breast milk, with an estimated RID of 0.30% and delayed mammary peak kinetics. High-sensitivity LC-MS/MS enabled reliable quantification even at minimal maternal doses. Although limited to a single case, these findings provide clinically relevant human pharmacokinetic data to support individualized breastfeeding counseling in everolimus-treated liver transplant recipients.